PEMIMPIN DALAM PERSPEKTIF ISLAM - Enizar, Enizar (STAIN Jurai Siwo Metro, 2004)
A Leader is very urgent in a community, from the smallest, more than two people to a big scale in a country. In Islam, especially from al-Hadits (tradition of Prophet Muhammad peace upon him) it indicates so urgent toward the problem of leader and leadership. The Prophet Muhammad gives direction and role started from criteria of a leader, essential of a leader to leaderâs obligation which is right of subordinates. All those roles indicate balance between demand toward every ono that aims to operate a duty with each position in that community.Keywords : a leader, Islam